2012
DOI: 10.1097/tp.0b013e31826784ad
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplantation Soluble CD30 Level As a Predictor of Acute Rejection in Kidney Transplantation

Abstract: The results of the meta-analysis show that the accuracy of pretransplantation sCD30 for predicting posttransplantation AR was poor. Prospective studies are needed to clarify the usefulness of this test for identifying risks of AR in transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…106,107 A meta-analysis concluded that the soluble CD30 marker showed only poor accuracy to predict acute rejection rates in the context of renal transplantation. 108 Another approach to assess cell-mediated immune responses is the measurement of intracellular adenosine-tri-phosphate production (iATP). Interestingly, individual levels of iATP correlated with rates of infections and cellular rejections in a meta-analysis of >500 solid organ transplant recipients, 109 independently of drug trough levels.…”
Section: Introductionmentioning
confidence: 99%
“…106,107 A meta-analysis concluded that the soluble CD30 marker showed only poor accuracy to predict acute rejection rates in the context of renal transplantation. 108 Another approach to assess cell-mediated immune responses is the measurement of intracellular adenosine-tri-phosphate production (iATP). Interestingly, individual levels of iATP correlated with rates of infections and cellular rejections in a meta-analysis of >500 solid organ transplant recipients, 109 independently of drug trough levels.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the pre-and post-transplant sCD30 concentrations were associated with a compromised kidney graft survival irrespective of antibody sensitization and HLA mismatches [51,59,60]. Although convincing data have been generated from the CTS trial, some other investigators were not able to repeat these findings [61][62][63]. This may be explained by differences in study designs, patients, and patient numbers.…”
Section: Scd30mentioning
confidence: 80%
“…The intra-individual variation of sCD30 over the post-transplantation period has been found to be considerable and differences in the immunosuppressive regimens, particularly in induction therapies, have been mentioned to contribute to biological variability [64,65]. A metaanalysis that was performed by Chen and colleagues challenged the finding that pretransplantation sCD30 was predictive of acute rejections [62]. An association between increased serum creatinine and sCD30 concentrations was reported, which brings up the question of…”
Section: Scd30mentioning
confidence: 95%
“…Ein signifikant schlechteres Organüberleben wurde beobachtet, wenn am Tag 30 nach Transplantation Konzentrationen > 40 U/mL vorlagen [49]. Die vielversprechenden Ergebnisse mit sCD30 ließen sich nicht immer reproduzieren [50][51][52], was unter anderem an der hohen intraindividuellen Variation des Markers liegen könnte [53]. Die sCD30-Konzentrationen schwankten um ca.…”
Section: Lösliches Cd30 Im Serum (Scd30)unclassified